Financial efficiency of microfinance institutions (MFIs) in the event of pre and post-financial crisis / Sarah Roslan - Roslan, Sarah (2021)
Microfinance Institutions (MFIs) have been recognised as effective tools for poverty eradication. Following the 2007–2009 financial crisis, the performance of the entire financial sector has gone through a very difficult situation. The crisis is due to the high default rate in the U.S. subprime home mortgage sector, where most borrowers failed to make regular payments. The crisis has proven to hamper economic growth including the banking sector. Since the MFIs nowadays form an integral part of the financial system, the impact is not exempted from the operation of the MFIs. Drop in financial revenue that resulted from the crisis disrupt the financial efficiency of the MFIs since financial revenue is the major source of income for MFIs to be sustained in the long run. This study proposes to determine the level of financial efficiency of the MFIs during pre and post-financial crisis as the first objective. Second, to examine the impact of firm characteristics on the financial efficiency level during both crisis events. Third, to investigate the effect of macroeconomic conditions on financial efficiency level during both crisis events. Data incorporated 166 MFIs from ASEAN 4 countries including Indonesia, Cambodia, Vietnam, and the Philippines from the year 2000–2007 (pre-crisis) and from the year 2010–2017 (post-crisis). The first stage of analysis measures the level of financial efficiency by using Data Envelopment Analysis. The second stage to identify firm characteristics and macroeconomic conditions on the financial efficiency level by applying Multivariate Panel Regression Analysis. The findings in the first stage analysis show the efficiency score of post-financial crisis is slightly higher from the efficiency score of pre-crisis period. This signifies the MFIs during both crisis events are financially efficient to sustain the operation in the long run. In the second stage, it appears mixed results where the firm characteristics and macroeconomic conditions are significant and insignificant to influence the financial efficiency of MFIs. The insignificant findings reveal the impact of the crisis has resulted that certain variables could not explain the variation in efficiency score in the first stage. Overall, the study will benefit microfinance industry that equip more preparation for any possible concurrence crisis in the future. This is important in providing continuous supports to the poor people, in compliance with the actual purpose of the MFIs – to alleviate poverty amongst the poor.